Effects of intra-hippocampal infusion of WAY-100635 on plus-maze behavior in mice - Influence of site of injection and prior test experience - Nunes-de-Souza, R. L.; Canto-de-Souza, A.; Rodgers, R. J. (Elsevier B.V., 2002)
The positive profile of systemically-administered 5-HT(1A) receptor antagonists in several rodent models of anxiolytic activity suggests an important role for postsynaptic 5-HT(1A) receptor mechanisms in anxiety. To test this hypothesis, we investigated the effects of WAY-100635 microinfusions (0, 0.1, 1.0 or 3.0 mug in 0.2 mul) into the dorsal (DH) or ventral (VH) hippocampus an behaviours displayed by male Swiss-Webster mice in the elevated plus-maze. As prior experience is known to modify pharmacological responses in this test, the effects of intra-hippocampal infusions were examined both in maze-naive and maze-experienced subjects. Test videotapes were scored for conventional indices of anxiety (% open arm entries/time) and locomotor activity (closed arm entries), as well as a range of ethological measures (e.g. risk assessment). In maze-naive mice, intra-VH (but not intra-M) infusions of WAY-100635 (3.0 mug but not lower doses) increased open arm exploration and reduced risk assessment. These effects were observed in the absence of significant changes in locomotor activity. In contrast, neither intra-VH nor intra-DH infusions of WAY-100635 altered the behaviour of maze-experienced mice. These Findings suggest that postsynaptic 5-HT(1A) receptors in the ventral (but not dorsal) hippocampus play a significant role both in the mediation of plus-maze anxiety in mice and in experientially-induced alterations in responses to this test. (C) 2002 Elsevier B.V. BY All rights reserved.
Keywords: 5-HT(1A) receptor; anxiety; dorsal hippocampus; ventral hippocampus; elevated plus-maze; mouse